Argatroban to achieve therapeutic anticoagulation in two patients with acute thrombosis and heparin resistance. Issue 8 (December 2019) - Mindlina, Irina; Nelmes, Elizabeth; Sharp, Megan; Butler, Andrew; Gudgin, Emma; Thomas, Will
Abstract : N/A: We present two cases where argatroban was successfully used in patients with acute thrombosis requiring anticoagulant treatment where heparin resistance with unfractionated heparin had been encountered. The first case was a woman with abdominal arterial thrombosis, of unknown cause, treated with therapeutic low molecular weight heparin that developed pulmonary embolism despite therapeutic anticoagulation (and had evidence of heparin resistance on anti-Xa monitoring). The second patient had provoked abdominal arterial thrombosis from sepsis and could not attain therapeutic anticoagulation with intravenous unfractionated heparin. In both cases therapeutic anticoagulation was achieved with the use of argatroban, as a temporizing measure to treat the acute thrombotic event. Conventionally, argatroban has been described for use in heparin-induced thrombocytopenia. The use of argatroban is briefly discussed, especially in the context of heparin resistance where anticoagulation can be challenging. Further research using argatroban in heparin resistant patients could be justified.